The Influence of Classical Guidance with a Mindfulness Approach on Reducing Academic Anxiety in Islamic Madrasah Schools - Hafid, Abd. (Moderasi : Journal of Islamic Studies, 2025)
This study aims to determine the effect of classical guidance using a mindfulness approach in reducing academic anxiety among grade XI students of MA Islamiyah Banjarjo Sumberrejo. The background of this research is the high level of academic anxiety experienced by students, particularly during learning activities and examinations. The research method employed was quantitative with a One Group Pretest-Posttest Design. The subjects were 27 students selected using a total sampling technique. The research instrument was an academic anxiety scale administered before and after the intervention. The treatment was carried out over eight sessions covering materials on academic anxiety, mindfulness, cognitive-behavioral techniques, deep breathing, and guided imagery. The results of the analysis showed a significant decrease in students’ academic anxiety levels after participating in classical guidance services with a mindfulness approach. Thus, this study concludes that classical guidance with a mindfulness approach is effective as an intervention to reduce students’ academic anxiety